Franz Wieacker. Private Law and Industrial Society. - Burillo Loshuertos, Jesús (GLOSSAE. European Journal of Legal History, 1988)
Wieacker, an eminent Romanist and legal historian, examines the relationship between the Codes and civil society in the light of recent German history which, to a large extent, extends to the whole of Western Europe, and raises the difficult question of the role of Roman law in the legal culture of the 19th century.